Writing quality of non-native MA thesis: perceptions and practices of examiners and students / Majid Fatahipour and Majid Nemati - Fatahipour, Majid; Nemati, Majid (Universiti Teknologi MARA, 2016)
Amongst extensive research on thesis writing quality, few provide a detailed account of common writing challenges/errors as perceived by examiners vs. students. In this study, eight recent English theses marked-up by examiners and defended in Iranian universities were selected randomly among those thesis made available (n=45). Based on an appraisal of comments written by examiners, a set of common challenges were drawn, which was confirmed by observations made by the researcher in viva voce sessions and then inspired questions about thesis writing quality. When administered to twenty examiners and seventy students, the most recurring themes in their practice were confirmed. The results draw a more precise picture, than previously available, of what examiners actually expect of a thesis and found four major areas of challenges in thesis writing, classified under lack of clarity in explaining, thesis formatting, grammatical errors and organisational inconsistencies. Findings also discussed the most significant practices in writing each chapter and reveal differences in perceptions of students/ examiners.